The interaction between tax evasion and tax supervision: Between deterrence and compliance - Khachab, Ayman (The International tax journal, 2025)
This study aims to highlight the complex relationship between tax evasion and tax oversight, focusing on the impact of regulatory measures in reducing evasion rates and enhancing tax compliance. It addresses the concept of tax evasion, its forms, and underlying causes, alongside a review of the tools and methods of tax supervision and their role in supporting the national economy. The study also analyzes the challenges faced by effective oversight, such as financial manipulation and technological advancements, while examining successful international experiences in this field. The study concludes with a set of recommendations to strengthen tax supervision, including digital transformation and the cultivation of a robust culture of tax compliance, in order to establish a more equitable and stable tax system.